Rendahnya Keterpilihan Perempuan pada Pemilu 2019 di Bali - Ni Made Ras Amanda Gelgel; Kadek Dwita Apriani (Universitas Udayana, 2019)
The results of the post-reform until the 2019 direct election showed that Bali had never succeeded in sending female representatives to the Indonesian Parliament. This paper discusses causes of the lackness of women candidates who succeced to gain chair in the national parliament. The paper uses supply-demand framework from Norris dan Lovenduski with qualitative method research. Demand side sees how political parties in Bali selected women to be their candidates discriminatively and not giving the same access to them. Supply side sees that women candidates in Bali get obstacles and constrains in various aspects such as (1) minimum financial ability, (2) lack of political experiences, (3) limited social networks, (4) limited time and space, (5) lack of motivation in political carrier. These cause an outcome of the lackness of women candidates being elected in the election.